Controlled synthesis of siloxane-siloxane block copolymers containing hydrophilic and hydrophobic segments - Chojnowski, J. (Polimery, 2022)
A method was developed to carry out a controlled synthesis of all-siloxane amphiphilic block copolymers, viz., by a sequential one-pot an-ionic ring-opening polymerization of cyclotrisiloxanes (Scheme 1). Usually, the hydrophobic block was first synthesized by Li alkyl- or Li silanolate-initi-ated polymerization of hexamethylcyclotrisiloxane, D3. After almost all the D3 had been converted, a cyclotrisiloxane was added that was carrying a precursor functional group at only one, or at each of the three silicon atoms (Schemes 2 and 5). When polymerized on the silanolate center, the cyclotrisiloxane yielded a block copolymer endowed with the precursor groups which subsequently became transformed into hydrophilic groups to yield the amphiphilic block copolymer. The hydrophilic block was also formed directly in the sequential copolymerization by using a cyclotrisiloxane with a hydrophilic function substituted for the precursor group. The present method allows to synthesize amphiphilic diblock or triblock all-siloxane copolymers that exhibit a high topological purity and a narrow molecular weight distribution. These copolymers can be precisely functionalized on one chain end.